2019
DOI: 10.1111/aogs.13579
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcome after complete uterine rupture

Abstract: Introduction Complete uterine rupture, a rare peripartum complication, is often associated with a catastrophic outcome for both mother and child. However, few studies have investigated large datasets to evaluate maternal outcomes after complete ruptures, particularly in unscarred uteri. This paucity of studies is partly due to the rarity of both the event and the serious outcomes, such as peripartum hysterectomy and maternal death. The incidence of uterine rupture is expected to increase, due to increasing ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…This study also revealed women who were para one were 88% less likely to have uterine rupture than women with multiparity. This finding is supported by different prior studies in different countries in Ethiopia 42 , Norway 8 , 69 , Senegal and Mali 56 , Uganda 51 , and Israel 70 . It might be attributed to the fact as increasing parity increases the elasticity and strength of the uterine muscle (Myometrium) decreases 38 , 71 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study also revealed women who were para one were 88% less likely to have uterine rupture than women with multiparity. This finding is supported by different prior studies in different countries in Ethiopia 42 , Norway 8 , 69 , Senegal and Mali 56 , Uganda 51 , and Israel 70 . It might be attributed to the fact as increasing parity increases the elasticity and strength of the uterine muscle (Myometrium) decreases 38 , 71 .…”
Section: Discussionsupporting
confidence: 81%
“…This finding was also in line with a systematic review and meta-analysis in both developing and developed countries conducted by WHO 58 . This might be due to the higher teenage pregnancies in the corresponding countries secondary to low education attainment 59 like in Ethiopia 60 , Uganda 61 , Niger 62 , India 63 and Mali 64 in which teenagers usually have less developed pelvic canal 69 67 and have low ANC utilizations 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%
“…The researchers discovered that, among women with an unscarred uterus, those aged over 35 years, having a parity of at least 3, being born in a non-Western country, and having a previous miscarriage before 12 weeks put them at a particularly high risk for rupture. Of greatest significance, they found that oxytocin has a higher odds ratio for rupture than induction with prostaglandins (6.5 and 4.5, respectively), and that the sequential use of prostaglandins and oxytocin had an odds ratio of 48 [10].…”
Section: Discussionmentioning
confidence: 99%
“…Morbidities related to uterine rupture include severe postpartum hemorrhage; almost half of these cases require blood transfusion, and 20% require hysterectomy. 9 Fetal and neonatal complications are also substantial, including up to 6% injury from hypoxic-ischemic encephalopathy up to 6%, neonatal intensive care admission in up to 50%, and fetal or neonatal death in up to 26% of cases. 10…”
mentioning
confidence: 99%